The impact of receiving an HIV diagnosis and cognitive processing on psychological distress and posttraumatic growth. - Nightingale, Vienna R; Sher, Tamara G; Hansen, Nathan B (Journal of traumatic stress, 2010)
This study examined human immunodeficiency virus (HIV) as a traumatic stressor, intrusive and deliberate cognitive processing, psychological distress, and posttraumatic growth. One-hundred twelve participants completed interviews on posttraumatic stress disorder (PTSD) Criterion A, Rumination Scale-Revised, Impact of Event Scale, and the Posttraumatic Growth Inventory; relationships were modeled using path analysis. Model 1 attempted to replicate prior empirical research, Model 2 attempted to empirically replicate part of the posttraumatic growth theoretical model, and Model 3 attempted to empirically replicate an integrated model of posttraumatic growth and traumatic stress theories. Model 3 had good fit with study data. Results suggest shared and separate pathways from traumatic stressor to psychological distress and posttraumatic growth, with pathways mediated by cognitive processing. Implications of findings are discussed.
Keywords: Acquired Immunodeficiency Syndrome; Adaptation, Psychological; Adult; Cognition Disorders; Female; HIV Seropositivity; Humans; Male; Middle Aged; Models, Psychological; Personality Inventory; Psychometrics; Sick Role; Stress Disorders, Post-Traumatic